Subpathotypes of avian pathogenic escherichia coli (apec) exist as defined by their syndromes and virulence traits - Maturana, Victor Gonçalves; de Pace, Fernanda; Carlos, Camila; Pires, Mathias Mistretta [UNESP]; De Campos, Tatiana Amabile; Nakazato, Gerson; Stheling, Eliana Guedes; Logue, Catherine M.; Nolan, Lisa K.; Da Silveira, Wanderley Dias (Bentham Science Publishers, 2011)
Avian pathogenic Escherichia coli (APEC) strains cause different types of systemic extraintestinal infections in poultry, collectively termed colibacillosis, which can cause significant economic losses in the poultry industry. To date, there have been no descriptions of genes or characteristics that allow for the classification of avian strains pathotypes responsible for causing specific diseases in their hosts. In this study we aimed to characterize avian E. coli strains representing 4 groups, including one of commensal strains (AFEC - Avian Fecal Escherichia coli) and 3 groups of APEC strains, where each group is responsible for causing a different disease syndrome in their respective hosts (septicemia, omphalitis and swollen head syndrome). We chose to examine several biological characteristics of these strains including: adhesion to eukaryotic cells, pathogenicity levels according to the lethal dose (50%) assay, phylogenetic group and virulence gene profiles. The comparison of strains based on these genotypic and phenotypic traits, using multivariate statisticals tools and complex networks, allowed us to infer information about the population structure of the studied groups. Our results indicate that APEC strains do not constitute a unique homogeneous group, but rather a structured set of subgroups, where each one is associated with a specific infectious syndrome which can possibly be used to define pathotypes or subpathotypes within APEC strains. These results offer new possibilities with which to study the genes responsible for various pathogenetic processes within APEC strains, and for vaccine development. It may be important to consider these subgroups when developing a vaccine in an effort for obtain cross protection, which has not yet been successfully accomplished when working with APEC strains.
Keywords: Apec; Escherichia coli; Network analysis; Pathotype